The Effect of Avgas and Ethanol Fuel Mixture on Fuel Spray Temperature - Rumani, Daniel Dewantoro; Putra, Dimas Endrawan; Cahyo, Dimas Hari; Ilminafik, Nasrul; Anam, Muhamad Khoirul (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to examine the effect of the avgas-ethanol fuel mixture on the fuel spray temperature. The research was carried out using a pressurized tube which was sprayed into the mock up which was assumed to be an aircraft combustion chamber with a pressure of 2 bar and a distance of 7,73 cm which would later be sprayed using pure avgas, a mixture of avgas and ethanol namely A80E20 and A60E40 then added with a temperature sensor at the end nozzle, center of jet, and impact wall. The spray temperature can result in incomplete combustion and result in higher exhaust emissions and also damage to the engine if it does not match the temperature capacity of the combustion chamber walls. The spray temperature results for the A60E40 fuel mixture are the lowest temperature, namely 25o-18.2oC and knowing that the more fuel is mixed, the lower the temperature of the fuel.